Composable data visualizations. (17th June 2021) - PETRICEK, TOMAS
Abstract : Abstract : Let's say we want to create the two charts in Figure 1. The chart on the left is a bar chart that shows two different values for each bar. The chart on the right consists of two line charts that share the x axis with parts of the timeline highlighted using two different colors.